If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3a + -4 = 11a + 5 Reorder the terms: -4 + 3a = 11a + 5 Reorder the terms: -4 + 3a = 5 + 11a Solving -4 + 3a = 5 + 11a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-11a' to each side of the equation. -4 + 3a + -11a = 5 + 11a + -11a Combine like terms: 3a + -11a = -8a -4 + -8a = 5 + 11a + -11a Combine like terms: 11a + -11a = 0 -4 + -8a = 5 + 0 -4 + -8a = 5 Add '4' to each side of the equation. -4 + 4 + -8a = 5 + 4 Combine like terms: -4 + 4 = 0 0 + -8a = 5 + 4 -8a = 5 + 4 Combine like terms: 5 + 4 = 9 -8a = 9 Divide each side by '-8'. a = -1.125 Simplifying a = -1.125
| 5-4=6 | | 0.4x+2.45=8.75 | | 4(y-9)32=6y-24 | | 4.62(x+8.25)=0 | | .6x-.1=.5x+3 | | 35-w=29 | | x=y+-20 | | (0)-3y=-9 | | 3x+15=(2x+2) | | 6(z-2)+3=-16(p-2) | | .6-.2=.5x+3 | | 4cosx=0 | | -2(15)= | | 1-3x^2=-3 | | 4a(x)+7b(x)=7.5 | | 40=3x-2 | | y=10sin(2t) | | -4x-2y=-6 | | 12.00-2.00p=3 | | -2(13+2)= | | 4a-1=3a+7 | | -2(13-(-2))= | | 5a-9+a=9 | | 3w^2-3w-5=0 | | 6=5-w | | -(x+8)=-x | | (p+1)(p-8)=0 | | x(-3+x)= | | (p+2)(p-4)=0 | | -3x-3y=66 | | a=13+-3b | | 3/4(3x+9)-6= |